2011
DOI: 10.1111/j.1742-4658.2011.08052.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D4 receptor oligomerization – contribution to receptor biogenesis

Abstract: Dopamine D 4 receptors (D 4 Rs) are G protein-coupled receptors that play a role in attention and cognition. In the present study, we investigated the dimerization properties of this receptor. Western blot analysis of the human D 4.2 R, D 4.4 R and D 4.7 R revealed the presence of higher molecular weight immunoreactive bands, which might indicate the formation of receptor dimers and multimers. Homo-and heterodimerization of the receptors was confirmed by co-immunoprecipitation and bioluminescence resonance ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Mutagenesis studies targeting the putative interaction interface of β 2 -adrenergic receptor showed that inhibiting β 2 dimerization caused its retention in the ER, thus supporting the hypothesis of receptor oligomerization in this cellular compartment (Salahpour et al, 2004). Other examples encompass the D 4 receptors (Van Craenenbroeck et al, 2011), GABA B receptors (MargetaMitrovic et al, 2000), and 5-HT 2C receptors (Herrick-Davis et al, 2006).…”
Section: Role Of Endoplasmic Reticulum (Er) and Chaperonesmentioning
confidence: 86%
“…Mutagenesis studies targeting the putative interaction interface of β 2 -adrenergic receptor showed that inhibiting β 2 dimerization caused its retention in the ER, thus supporting the hypothesis of receptor oligomerization in this cellular compartment (Salahpour et al, 2004). Other examples encompass the D 4 receptors (Van Craenenbroeck et al, 2011), GABA B receptors (MargetaMitrovic et al, 2000), and 5-HT 2C receptors (Herrick-Davis et al, 2006).…”
Section: Role Of Endoplasmic Reticulum (Er) and Chaperonesmentioning
confidence: 86%
“…Functional significance of these repeats has been suggested in many studies (Van Tol et al, 1992; Asghari et al, 1994, 1995; Schoots and Van Tol, 2003; Van Craenenbroeck et al, 2005, 2011). For example, the 7R has been linked to suppressed DRD4 expression in vitro (Schoots and Van Tol, 2003).…”
Section: Drd4 Exoniii Vntrmentioning
confidence: 93%
“…Besides interacting with numerous ER-resident folding assistants GPCRs can self associate in the ER forming GPCR homo-and heteromers which under some circumstances might have a chaperone-like activity defining the receptor's export profile [62,65,66]. Alternatively, GPCRs can interact in this organelle with accessory proteins (e.g., RAMP, MRAP, RanBP2, MRAP, etc.)…”
Section: Modulation Of Gpcr Biology By Gipsmentioning
confidence: 99%